Red for danger: the effects of red hair in surgical practice. (9th December 2010) - Cunningham, Andrew L; Jones, Christopher P; Ansell, James; Barry, Jonathan D
Abstract : Jonathan D Barry and coworkers discuss the validity of the unique surgical requirements of patients with red hair